Antz - Darnell, Eric.; John, Tim.; Dreamworks Pictures; Pacific Data Images (Universal City, Calif. DreamWorks Home Entertainment ; distributed in the Philippines by MagnaVision, 2004)
When Z convinces his soldier buddy Weaver to switch places with him, his simple life takes a wild turn. One of the most insignificant workers, Z may just turn out ot be the biggest hero of them all.
Originally released as a motion picture in 1998.
Music by Harry Gregson-Williams, John Powell ; screenplay by Todd Alcott, Chris Weitz, Paul Weitz ; executive producers, Penney Finkelman Cox, Sandra Rabins, Carl Rosendahl ; produced by Brad Lewis, Aron Warner, Patty Wooton ; directed by Eric Darnell, Tim Johnson.
Voices: Woody Allen, Dan Aykroyd, Anne Bancroft, Jane Curtin, Danny Glover, Gene Hackman, Sylvester Stallone, Sharon Stone, Christopher Walken.
VCD, anamorphic widescreen, 5.1 surround, Dolby surround, Digital surround play requires the use of a DTS Decoder.
In English
Keywords: Families; Ants -- Drama